The Concept of Prophethood According to al-Alusi in his book of Tafsir Rūḥ al-Maʿānī - Achmad Dahlan (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This research examines the concept of Prophethood (Nubuwwah) according to Mahmud al-Alusi as presented in his exegetical work Rūḥ al-Maʿānī. The study analyzes his comprehensive perspective on Prophethood and evaluates both the strengths and limitations of his thought on the subject. Employing a descriptive-analytical approach, the research collects and examines data from Al-Alusi’s tafsir alongside relevant authoritative scholarly sources in order to achieve its objectives. Particular attention is given to Quranic verses related to Prophethood and Al-Alusi’s interpretations of them. The study concludes that Al-Alusi developed a holistic understanding of Prophethood, regarding it as a lofty divine institution that integrates spiritual and moral perfection. He emphasized the role of Prophethood in the purification of the human soul and the cultivation of noble character, while presenting the Prophet Muhammad (peace be upon him) as the supreme model for humanity. Although Al-Alusi maintained a balance between reason (ʿaql) and transmitted tradition (naql), his interpretations were at times influenced by Sufism and philosophy, which occasionally resulted in ambiguity in his presentation. Moreover, the study finds that his exegetical approach does not sufficiently engage with several modern intellectual debates concerning Prophethood and revelation, thereby limiting its applicability within contemporary intellectual discourse.